2021
DOI: 10.3390/ani11041025
|View full text |Cite
|
Sign up to set email alerts
|

Successful Insulin Glargine Treatment in Two Pet Guinea Pigs with Suspected Type 1 Diabetes Mellitus

Abstract: Scientific information on spontaneous type I diabetes mellitus (DM) and treatment modalities in guinea pigs is scarce. As most diabetic guinea pigs are overweight and respond to dietary changes, a disorder resembling type II-DM in humans seems to be most prevalent in this species. In the present report, a nine-month-old female intact guinea pig (GP1) was presented because of a cataract and polyphagia. The physical examinations in GP1 and its littermate, GP2, were unremarkable. Laboratory tests revealed hypergl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Matschinsky and Wilson (18) , working with mouse ear epidermis, discovered that estrogens stimulate glucokinase enzyme system, resulting in greater glucose absorption by cell. Kreilmeier-Berger et al (19) has demonstrated that 1-thryoxine enhances glucose as simulation & aerobic glycolysis in guineapig whole skin preparations. Failure of intralesional insulin to affect delayed responses indicates that local impact of insulin is to some extent specific for acne inflammation & does not support notion that delayed tuberculin allergy plays role in pathogenesis of acne.…”
Section: Intralesional Insulin In Oral Lichen Planus (Olp)mentioning
confidence: 99%
“…Matschinsky and Wilson (18) , working with mouse ear epidermis, discovered that estrogens stimulate glucokinase enzyme system, resulting in greater glucose absorption by cell. Kreilmeier-Berger et al (19) has demonstrated that 1-thryoxine enhances glucose as simulation & aerobic glycolysis in guineapig whole skin preparations. Failure of intralesional insulin to affect delayed responses indicates that local impact of insulin is to some extent specific for acne inflammation & does not support notion that delayed tuberculin allergy plays role in pathogenesis of acne.…”
Section: Intralesional Insulin In Oral Lichen Planus (Olp)mentioning
confidence: 99%
“…Furthermore, this study reported an improvement in HbA1c. Additionally, N. gaditana attenuated glycosuria and polyphagia which marked its potential in reversing diabetic complications [ 184 , 185 ]. These effects were credited to the modulatory effect on pancreatic β-cell insulin secretion, thus improving glucose metabolism.…”
Section: Effect Of Microalgae On Diabetes Mellitusmentioning
confidence: 99%